'Post‐Third‐World City' or Neoliberal 'City of Exception'? Rio de Janeiro in the Olympic Era. (30th July 2016) - Aaron Richmond, Matthew; Garmany, Jeff
Abstract: This article considers processes of urban development within the context of mega‐event preparations in Rio de Janeiro. We begin with a brief overview of these development processes, highlighting their connections to political and economic change in recent years. Proponents of these mega‐event‐led initiatives argue that Rio is undergoing a period of inclusive growth and integration: a perspective we call here a 'post‐Third‐World city' narrative of urban renewal. Critics, however, contend that urban officials are harnessing mega‐events (e.g. the 2014 World Cup and the 2016 Olympic Games) to push forward a neoliberal agenda of socially unjust policies benefiting the interests of capital and marginalizing the city's poor and especially its favelas (i.e. the 'city‐of‐exception' thesis). In this article we explore the insights of these two perspectives and consider why they have grown popular in recent years. Though we side generally with the city‐of‐exception thesis, we argue that important geographic and historical particularities must also be accounted for. Without carefully situating analytical perspectives empirically—in particular, cases in which theoretical models are drawn from European and North American contexts—urban researchers risk concealing more than they reveal in analyses of rapidly developing countries like Brazil.